Fantasy Fishing Coperation / Mohamad Zulkarnain Jaafar ... [et.al]. - Jaafar, Mohamad Zulkarnain; Mohd Noh, Siti Rohayu; Khalid, Norazian; Yahya, Shulieyani; Sakri, Aisha Murni (Faculty of Hotel and Tourism Management, 2001)
"FANTASY FISHING COORPERATION", is the one of the business that has been connected by the Outdoor Fresh Fish Pond Water Park and provides you the angling activities that can give you a lot of fun and good activities for you to enjoy. Suitable with the name that has been given by our company that is Fantasy Fishing it can give you a better service and it also can fulfill the demand of the angling activities, especially among our peoples who like this hobbies. The other company developed this business since 1998 to 1999. During this year, this type of business becomes larger and the other competitors also have commercialized it. But since this year, this business become lower and many competitors was not doing this business again. This situation has given us a chance to try and developed this business, because we think that this business can give us more profit and benefit. This competitors maybe don't know how too large and commercialize their business, and this statement telling you that, a strategic planning is more important to develop a better business in the future.